Connecting with Families through Virtual Perinatal Education during the COVID-19 Pandemic. Issue 6 (November 2020) - Pasadino, Francine; DeMarco, Kathleen; Lampert, Elizabeth
Abstract : Abstract: The COVID-19 pandemic has caused many changes in health care. The status quo has been upended. We have been challenged in many ways to maintain our ability to meet the needs of our clients while keeping them safe. The Center for Perinatal Education and Lactation at NYU Langone Hospitals, in one of the initial epicenters of the pandemic in New York City, had to abruptly transition the childbirth education program to a virtual format in March of 2020. The goal for this change was to continue to provide evidence-based support and guidance our to our expectant and new families through this crisis. This report focuses on the process and challenges of transitioning to and implementation of the virtual format in the context of the COVID-19 crisis. We discuss the rapidly evolving programmatic changes to our approach and reflect on the themes and changing landscape of our newly structured model. Questions and answers live discussion webinars "Ask the Educator" on various topics were a valuable tool in connecting with families and allaying anxiety and fear. Abstract : Many changes to maternity care have been initiated as a result of the COVID-19 pandemic. New York City was one of the initial epicenters of the virus in the United States. In this article, nurses from a hospital system in New York City share their experiences in abruptly transitioning all of their perinatal education classes to a virtual format to meet the needs of their patients while keeping them safe.